Economic governance : guidelines for effective financial management (UN New YorkUS, 2000)
Explains the basic canons of good economic governance with special emphasis on efficacious financial techniques, applicable primarily to developing countries and transitional economies.
Keywords: FINANCIAL MANAGEMENT